In situ and ex situ soil respiration in natural, Acacia-invaded and cleared riparian ecotones in the Fynbos Biome - Kambaj Kambol, Oliver (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScConEcol)--Stellenbosch University, 2013.